Using claims and evidence to support the search for extraterrestrial life: teacher reflections following an interdisciplinary English–science argumentation unit. Issue 2 (15th March 2019) - Summers, Ryan; Rodems, Kathy; Denos, Sharlene; Atkinson, Amy
Abstract: The Next Generation Science Standards identifies argumentation as a central practice, and, subsequently, energizes teachers to develop students' capacity to write well-reasoned arguments and support their claims with relevant evidence. These skills now expected in the science classroom have long been central to instruction in English-language arts. This article overviews the design and delivery of a first-time interdisciplinary collaboration between three teachers, representing English language arts, science, and a teacher-librarian. Their integrated unit was based on principles of scientific argumentation. Recounting the experience from the perspectives of the teachers, and informed by observations and interviews conducted, discussion centers on the practical aspects of unit delivery and meeting intended goals. This article thematically explores qualitative data collected from the teachers, including individual reflections and a focus group interview, as well as classroom observation and student post-unit survey data. Drawing on the experience from the inaugural implementation, we discuss considerations for future efforts and implications for the broader audience.